THE INFLUENCE OF ORGANIZATIONAL CULTURE, AND WORK ENVIRONMENT ON GENERATION Z EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AT PT PERMODALAN NASIONAL MADANI SOUTH JAKARTA OFFICE - Arsyah Ali Widiandana; Wilfridus B. Elu (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research is motivated by the gap in the performance of Generation Z employees at PT Permodalan Nasional Madani South Jakarta Office, as indicated by the results of the 2023 performance evaluation. The main problems include the achievement of targets that have not been optimal, the quality of work that has not met the standards, and the lack of punctuality and work independence. The purpose of this study was to analyze the effect of Organizational Culture and Work Environment on Generation Z Employee Performance through Work Motivation. The study used a quantitative approach with a survey method. The research sample amounted to 147 Generation Z employees, selected using simple random sampling technique. Data collection was done through a questionnaire with a Likert scale. Data analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of SmartPLS 3 software. The results showed that Organizational Culture has a positive and significant effect on Work Motivation with a P-value of 0.000 <0.05. Work Environment has a positive and significant effect on Work Motivation with a P-value of 0.000 <0.05. Work Motivation has a positive and significant effect on Employee Performance with a P-value of 0.042 <0.05. Organizational Culture has a positive and significant effect on Employee Performance with a P-value of 0.000 <0.05. Work Environment has a positive and significant effect on Employee Performance with a P-value of 0.028 <0.05. Organizational Culture does not mediate Employee Performance through Work Motivation with a VAF value of 16.6% < 20%. Work Environment partially mediates Employee Performance through Work Motivation with a VAF value of 38% between 20%-80%.